2022
DOI: 10.1186/s12974-022-02539-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of C5a–C5aR1 signaling alters the dynamics of AD progression

Abstract: Background The complement system is part of the innate immune system that clears pathogens and cellular debris. In the healthy brain, complement influences neurodevelopment and neurogenesis, synaptic pruning, clearance of neuronal blebs, recruitment of phagocytes, and protects from pathogens. However, excessive downstream complement activation that leads to generation of C5a, and C5a engagement with its receptor C5aR1, instigates a feed-forward loop of inflammation, injury, and neuronal death, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 108 publications
6
37
1
Order By: Relevance
“…C3 has been shown to be involved in synapse pruning (19)(20)(21)44) C3 staining, using an antibody that recognizes whole C3 as well as its cleavage products, was observed mainly on astrocytes and deposited on the neuropil. Our results showed a high amount of C3 positive astrocytes, mainly in the vicinity of amyloid plaques (data not shown), which parallels previous bulk RNAseq and IHC results from our lab showing a strong astroglial response (characterized by an increased in GFAP and C3) in the hippocampus of Arctic and Arc-C5aR1KO mice at 7 and 10 months of age (35). Here, our results at 10 months in the CA3-SL region showed a significant increase of C3 puncta (excluding astroglia-associated C3) in the Arc mice when compared to WT littermates, which was further increased in the Arc-C5aR1KO mice…”
Section: Absence Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…C3 has been shown to be involved in synapse pruning (19)(20)(21)44) C3 staining, using an antibody that recognizes whole C3 as well as its cleavage products, was observed mainly on astrocytes and deposited on the neuropil. Our results showed a high amount of C3 positive astrocytes, mainly in the vicinity of amyloid plaques (data not shown), which parallels previous bulk RNAseq and IHC results from our lab showing a strong astroglial response (characterized by an increased in GFAP and C3) in the hippocampus of Arctic and Arc-C5aR1KO mice at 7 and 10 months of age (35). Here, our results at 10 months in the CA3-SL region showed a significant increase of C3 puncta (excluding astroglia-associated C3) in the Arc mice when compared to WT littermates, which was further increased in the Arc-C5aR1KO mice…”
Section: Absence Ofsupporting
confidence: 92%
“…Previous studies in our lab and others, have shown that the genetic or pharmacological inhibition of C5a-C5aR1 signaling reduced pathology, and rescued synaptic and cognitive loss in several mouse models of AD (31)(32)(33)(34)(35), suggesting that C5a-C5aR1 signaling might be a better therapeutic target than blocking the upstream components of the complement cascade. Moreover, two different C5aR1 antagonist have already been proven safe in humans in different clinical trials for autoimmune disorders, further emphasizing the potential for C5aR1 as a therapeutic target (36,37).…”
Section: Introductionmentioning
confidence: 73%
“…2-photon in vivo studies can be used to overcome this limitation in future studies. Additionally, since only female mice were used for the present study, possible microglial sex-specific changes in response to PMX205 should be assessed, although genetic ablation of C5aR1 in another mouse model of amyloidosis (Arctic) did not show sex-related effects in behavior, gliosis or gene expression in either the AD characteristics or the effect of a deletion of C5aR1 [ 17 , 21 ]. Finally, peripheral inflammation certainly can affect the progression of AD-pathology ([ 81 , 82 ] and reviewed in [ 83 ]), and it remains to be seen what the contribution of PMX205 mediated peripheral effects may be.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported a neuroprotective role of C1q in the absence of triggering downstream activation [ 12 , 13 ], but we and others have also demonstrate a beneficial effect of a genetic ablation of C1q, C3 and CR3 in AD mouse models [ 14 16 ]. In addition, C3a is generated upon complement activation and binds to C3aR, whose expression is induced in microglia in mouse models of amyloidosis including very clear tissue and temporal induction recently published by this lab [ 17 ]. Both in the brain and in the periphery, C3a-C3aR signaling can be either pro- or anti-inflammatory depending on the developmental or disease state [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the process of AD disease, excessive activation of downstream complement will lead to the production of C5a, which can bind with the receptor and cause a series of negative reactions such as inflammation, injury and neuronal death ( Ager et al, 2010 ). It has been shown that in AD, the C5a-C5aR1 signaling pathway can accelerate disease progression by enhancing the activation of microglia and exacerbating neuroinflammation ( Carvalho et al, 2022 ). In the process of finding an effective treatment for AD, people found that sigma1 receptors (S1Rs) may regulate AHN, prevent Aβ-induced neurotoxicity and modulate the pathophysiology of AD, and have great potential as new targets for treatment ( Penke et al, 2018 ; Ma et al, 2021 ).…”
Section: Key Mechanisms Of Altered Ahn In Alzheimer’s Diseasementioning
confidence: 99%